Implementing Local Wisdom Values in Bride and Groom Course at KUA Bara SubDistrict, Palopo City - Dodi Ilham (P3I Luwu Raya, 2019)
This study aims to determine how the bride and groom course in KUA Bara Subdistrict, Including the values of local wisdom in implementing the bride and groom course, and inhibiting factors and supporting local wisdom values. This research is research with a qualitative approach to field research. This research is located in KUA Kec. Palopo City Bara. This study's data sources are primary data sources (course participants for bride and groom), secondary data sources (KUA Bara Subdistrict files). Data collection techniques through interviews, observation, and documentation. The data analysis used was descriptive qualitative data analysis. The data obtained that the implementation of the course for the bride and groom in KUA Kec. Palopo City Bara is administratively by the General Director of Islamic Community Guidance Regulation on Candidate Bride Course Number DJ.II / 491 of 2009 dated December 10, 2009, although, in the process of implementing the bride and groom course, it is still not by the Regulation of the Director-General of Islamic Community Guidance of the Ministry of Religion Number DJ.II/542 of 2013 concerning Guidelines for the Implementation of Pre-Marriage Courses; The values of local wisdom are conveyed by the method of lectures and questions and answers between the resource person and the prospective bride and groom at KUA, Bara Subdistrict, Palopo City, with a focus on three values of local wisdom, namely aju tunung (wood/birth support), waju (clothes/honor), aju-aju (inner sustenance); Supporting Factors for the implementation of the bride and groom course at KUA Kec. Bara Kota Palopo is the resource persons' ability for the prospective bride and groom course to insert local wisdom values for the bride and groom's course material. The bride and groom are serious about receiving the bride and groom's course materials.